PREVALENSI PENURUNAN TEKANAN DARAH PADA PASIEN DENGAN ANESTESI SPINAL MENGGUNAKAN BUPIVAKAIN 0,5% PADA TINDAKAN SECTIO CAESAREA DI RSUD dr. H. CHASAN BOESOIRIE TERNATE - Idrus, Shakila; Singal, Peter H.Y; Pattiha, Abdul M. (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Spinal anesthesia can cause complications such as hypotension and nausea and vomiting. Hypotension in caesarea sectio in reported to be 80%. Bupivacaine is the local anesthesia that is the class of amide commonly used in spinal anesthesia. The study aimed to determine the prevalence of lowering blood pressure in the patient with spinal anesthesia by using bupivacaine 0,5% in caesarea sectio at Dr. H. Chasan Boesoerie hospital. Retrospective descriptive observational study using secondary data in medical records at Dr. H. Chasan Boesoerie hospital in 2020. The result of the research based on age mostly in >30 years as many as 57,0%, height 151-160 cm 54,0%, blood pressure in the fifth minutes and fifteenth minutes, there was the decrease in 83% on systolic blood pressure and as many as 46,0%) on diastolic blood pressure. Patients with spinal anesthesia based on age were mostly in >30 years, the most common height was 151-160 with a dose of 10 mg bupivacaine. It was found that at the fifth minutes the most decreased blood pressure was found